2000
DOI: 10.1177/031289620002500305
|View full text |Cite
|
Sign up to set email alerts
|

The Information Content of Losses: Shareholder Liquidation Option and Earnings Reversals

Abstract: Using Australian data this paper investigates the information content of losses. We are motivated by the possibility that losses and profits have different associations with share returns because losses are not expected to be permanent. Consistent with the evidence in Hayn (1995), our findings show that share returns do have a lower association with losses. In particular, we extend Hayn (1995) and focus on losses made by financially healthy firms where we provide an explanation for the low ERC for these losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Evidence from the US market is consistent with the market inefficiently assessing the probability of loss reversal (Dhaliwal et al, 2013;. Furthermore, Sin and Watts (2000) find market response to earnings to be weaker for Australian firms with more persistent loss. This evidence can be interpreted as Australian investors underreacting to persistent losses.…”
Section: Hypothesis Developmentmentioning
confidence: 56%
See 2 more Smart Citations
“…Evidence from the US market is consistent with the market inefficiently assessing the probability of loss reversal (Dhaliwal et al, 2013;. Furthermore, Sin and Watts (2000) find market response to earnings to be weaker for Australian firms with more persistent loss. This evidence can be interpreted as Australian investors underreacting to persistent losses.…”
Section: Hypothesis Developmentmentioning
confidence: 56%
“…Therefore, assessing the probability of loss reversal is useful for investors deciding on whether to abandon the firm (Joos and Plesko, 2005). Sin and Watts (2000) examine the valuation of loss firms in Australia. They argue that, for firms that subsequently become profitable, investors are more likely to treat losses as transitory earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In fourth hypothesis, we showed that there is a positive and significant relationship between the probability of loss making companies being profitable in future periods and abnormal stock returns. In this regard, Sin and Watts (2000) also evaluated loss-making companies in Australia and showed that investors of loss making companies that eventually become profitable treat losses as a volatile item, since the impact of loss reversal on stock prices is visible positively and significantly. In addition, Collins and Hirbar (2002) and Chen et al (2011) and Joos and Plesko(2005) showed that the relationship between negative earnings and stock prices and performance is inverse, however, when there is a probability of loss reversal, return on equity will have incremental rate due to positive changes in the stock price.…”
Section: Comparing the Results Of Assumptions With Performed Investigmentioning
confidence: 99%
“…(Joos & Plesko, 2005). Sin and Watts (2000), assessed the loss-making companies in Australia and showed that investors of loss-making companies that eventually become profitable, treat the losses as a volatile item. They found that the relationship between the loss and stock returns for those loss-making companies that have experienced high loss reversal is less important.…”
Section: Studies To Develop Hypotheses About the Loss Reversal Model mentioning
confidence: 99%